ISLAM DAN BUDAYA LOKAL (PLURALISME AGAMA DAN BUDAYA DI INDONESIA) - Muhammad Fatkhan Muallifin (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
A good mentor needs to have an interest in working with people. Pluralism cannot be understood simply by saying that society is plural and diverse, because this will make people live compartmentalized in rigid and inclusive sentiments and fanaticism. Moreover, pluralism in religion, which so far has created an attitude of suspicion, mutual accusations, and wrongful blaming, so that it broke out into conflict. This is mostly due to the absence of an attitude of getting to know each other and understanding the true meaning of differences. The method used is a literature review that discusses Islam and Local Culture (Religious and Cultural Pluralism in Indonesia). Where Pluralism must be understood as a true bond of diversity in the bonds of national civilization and even as a savior of mankind. In the life of the nation and state, the relationship between religious and cultural pluralism in Indonesia is emphasized, especially to overcome the problems arising from the impact of this relationship. The solution to addressing the problem of religious and cultural pluralism in Indonesia, among other things, is found in the Al-Quran surah Al Hujurat verse 13 and Asy Syuura' and realizing the declaration of the Medina charter as in the time of the Prophet Muhammad SAW in fostering community relations between religious communities, acknowledging the differences and identities of each religion. -respectively.